Evaluation Report on Essential Supplies Programme - Planning Commission (Planning Commission, 1985)
The New 20-Point Programme was announced on 14th January, 1982. Within month of its launching, the Planning Commission asked the Programme Evaluation Organisation to evaluate its Point no. 17, viz., the Essential Supplies Programme, which stated that the Government would “expand the public distribution system through more fair price shops, including mobile shops in far-flung areas and shops to eater to industrial workers, students' hostels and to make available to students text-books and exercise books on a priority basis and to promote a strong consumer protection movement.’’ The present study was accordingly planned and conducted to evaluate the Essential Supplies Programme and the specific aspects of the public distribution system on which it is focused.
Programme Evaluation Organisation Planning Commission
Programme Evaluation Organisation Planning Commission